2016
DOI: 10.1073/pnas.1605036113
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning direct and indirect effects reveals the response of water-limited ecosystems to elevated CO2

Abstract: Increasing concentrations of atmospheric carbon dioxide are expected to affect carbon assimilation and evapotranspiration (ET), ultimately driving changes in plant growth, hydrology, and the global carbon balance. Direct leaf biochemical effects have been widely investigated, whereas indirect effects, although documented, elude explicit quantification in experiments. Here, we used a mechanistic model to investigate the relative contributions of direct (through carbon assimilation) and indirect (via soil moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
129
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 120 publications
(146 citation statements)
references
References 78 publications
(77 reference statements)
9
129
0
Order By: Relevance
“…While the higher ET under CO 2 fertilization would be expected to deplete soil water, we found no appreciable changes in SWC of the top 10 cm of soil (+0.0013, 0.0007, and 0.0019 m 3 /m 3 ), even for cases where summertime precipitation decreased or remained similar (CNRM‐CM5 and AVE). These results are consistent with Fatichi, Leuzinger, et al () who showed that increased WUE supports a higher LAI through soil water savings but leads to a more rapid consumption of SWC due to the increased vegetation. The effects of increased CO 2 on gains in NEP despite a similar SWC when compared to scenarios without fertilization is attributed to ecosystem alterations in water use efficiency (WUE = GPP/ET, Figure d), which increased substantially (+68%, 42%, and 69%) at the expense of higher summertime interannual variability.…”
Section: Resultssupporting
confidence: 92%
“…While the higher ET under CO 2 fertilization would be expected to deplete soil water, we found no appreciable changes in SWC of the top 10 cm of soil (+0.0013, 0.0007, and 0.0019 m 3 /m 3 ), even for cases where summertime precipitation decreased or remained similar (CNRM‐CM5 and AVE). These results are consistent with Fatichi, Leuzinger, et al () who showed that increased WUE supports a higher LAI through soil water savings but leads to a more rapid consumption of SWC due to the increased vegetation. The effects of increased CO 2 on gains in NEP despite a similar SWC when compared to scenarios without fertilization is attributed to ecosystem alterations in water use efficiency (WUE = GPP/ET, Figure d), which increased substantially (+68%, 42%, and 69%) at the expense of higher summertime interannual variability.…”
Section: Resultssupporting
confidence: 92%
“…Trait‐based approaches typically offer a better representation of ecosystem functioning than models grouping plant traits into broad categories (Pappas et al, ). T&C has been successfully applied to simulate water and carbon fluxes in various ecosystems worldwide (Fatichi & Ivanov, ; Fatichi et al, ; Fatichi, Leuzinger, et al, ; Manoli et al, ; Paschalis et al, , ; Pappas et al, ) and is applied here in a revised form to the Amazon rainforests. Consistently with other DGVMs (Restrepo‐Coupe et al, ), in the case of evergreen biomes the original formulation of T&C does not simulate a phenologic cycle of photosynthetic efficiency, which is maintained fixed throughout the year.…”
Section: Methodsmentioning
confidence: 99%
“…Le Bauer & Treseder, ). While indirect effects through water savings (due to reduced stomatal conductance under increasing [CO 2 ]) could contribute to increased NPP (Donohue et al ., ; Fatichi et al ., ), the C sink of intact vegetation must show a progressive attenuation in the long term according to results of TBMs that account for N and phosphorus cycles (Zaehle et al ., ; Wieder et al ., ).…”
Section: Discrepancy In Predicting the Effects Of Rising [Co2] On Thementioning
confidence: 99%